2016
DOI: 10.1055/s-0036-1581064
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Orbital Roof Repair with Titanium Mesh in a Case of Traumatic Intraorbital Encephalocele: A Case Report and Review of Literature

Abstract: Orbital roof fractures associated with cranial and maxillofacial trauma are rarely encountered. Traumatic intraorbital encephaloceles due to orbital roof fractures developing in the early posttraumatic period are even rarer. A variety of materials, such as alloplastic implants or autogenous materials, have been used for the reconstruction of orbital roof, but data regarding the long-term results of these materials are very limited. We report a case of intraorbital encephalocele developing in the early posttrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A total of 52 patients were included in the final analysis for the systematic review including the patient presented herein 3–5,7–38. These case reports ranged in date from 1951 to 2022 and included between 1 and 6 patients per report.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 52 patients were included in the final analysis for the systematic review including the patient presented herein 3–5,7–38. These case reports ranged in date from 1951 to 2022 and included between 1 and 6 patients per report.…”
Section: Resultsmentioning
confidence: 99%
“…Repairs are commonly performed for fractures following high-impact trauma using titanium plating or micromesh with screws to fixate the material as required, however bone and cartilage autografts may also be used [ 8 , 9 ]. Despite the commonly described approaches of utilizing titanium mesh or autografts, we found that using an irradiated homologous cadaveric rib cartilage graft negates the need for autologous harvest, which is associated with morbidities and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Decompressive craniectomy (DC) is the main method for rapidly reducing intracranial pressure (ICP) in patients with ASDH [6], but acute encephalocele often occurs suddenly during DC surgery, leading to higher mortality and morbidity, in this study, we can found the mortality rate of observation group 73.91% was higher than the control group 13.04%. Previous studies have suggested that delayed traumatic intracranial hematoma (DTIH), post-traumatic acute diffuse brain swelling (PADBS) and intracranial venous reflux disorder are the main factors affecting the acute encephalocele during surgery [7]. In this paper, related preoperative clinical data and CT image information were used to assess the occurrence of intra-operative acute encephalocele, so as to provide a basis for the developent of a more scientific and reasonable treatment strategy for ASDH patients.…”
Section: Discussionmentioning
confidence: 99%